An analysis of injury patterns of abdominal trauma in patients attending surgical emergency department of rural hospital, Karnataka, India - Krishnappa, Narasimhaiah; Khan, Asif; Sakranaik, Saraswathi (International Surgery Journal, 2017)
Background: Globally, abdominal trauma is a major public health problem irrespective of socioeconomic levels. Severe blood loss and infection are the serious complication of any abdominal trauma. A detailed assessment for early identification and prompt management is required to reduce the mortality and morbidity in any abdominal trauma. Hence this study was designed to assess the incidence and patterns of abdominal injuries in trauma patients. Methods: It was assorted and identified the incidence and sub type of abdominal injuries and associated trauma, and identified variables related to morbidity and mortality. Results: A total of 150 abdominal trauma cases were analyzed; 103 patients with blunt abdominal trauma and 47 with penetrating. The most frequent type of abdominal trauma was blunt trauma; its most common cause was motor vehicle accident. Most abdominal trauma patients presented with other injuries, especially patients with blunt abdominal trauma. Mortality was higher among penetrating abdominal trauma patients. Conclusions: Type of abdominal trauma, associated injuries, and Revised Trauma Score are independent risk factors for mortality in abdominal trauma patients.